5 How do we know that we know something?. Issue Volume 24:Issue Supplement 1(2019) (July 2019) - Fajardo Flores, Carlos José; Alger, Jackeline
Abstract : In high income countries, this question may be substituted by another one that it's easier to answer: How many randomized controlled trials have been done over this topic? In Honduras, Central America, this question is answered very differently. Medical practice in LMIC continues to be empirical and anecdotic and in the best-case scenario, decisions are taken based on research made abroad under distinct settings. Dealing with endless challenges, our health system fails to inform operational, implementation and health system research decisions. Barriers that limit quality research go from untrained health workers to lack of funding to come up with more complex research designs. Descriptive studies represent an overwhelming majority of published studies but due to their nature, their impact falls short to inform health decisions that benefit those that need it the most. So, are we posing quality research studies that answer our most important clinical questions? The EBM manifesto enlists the most important challenges that need to be addressed. Increase the systematic use of evidence is one of them. An estimated 97% of research in the world seeks to produce new knowledge, only the remaining 3% seeks to implement existing knowledge. Implementation Research (IR) is a discipline that aims to uptake interventions that have been proven effective under controlled settings and turn them into routine practices that benefit a wider population. Let's consider EBM as an effective intervention to enhance quality research practice, then why in LMIC an EBM culture has not been implemented? What factors have diminished its impact? IR might be an important tool to uptake the implementation of EBM in a poor developed research context. Pose research questions that arise in the communities, in real not controlled settings, that try to solve day-to-day problems can make the research process a less cumbersome enterprise. In other words, more practical questions that are closer to reality can boost a research practice that motivates a scientific community that watches research more as a luxury than as a necessity. A powerful way to motivate a scientific community to uptake research is to prove with evidence that through evidence itself is the most effective, secure and ethical way of practicing medicine. Even though the outlook is not encouraging, showing the importance of EBM must be the first step to change the empirical paradigm, where a doubt is perceived as a weakness and not as an opportunity. Online mentorship might be a practical solution to close the gap between poor developed and well-developed EBM environments. A personal experienced mentor could encourage and guide a young researcher to improve research quality and integrity. Asking the right questions, declaring conflicts of interests, statistical significance and reporting bias should be part of a checklist that could be revised together online. At the Universidad Nacional Autónoma de Honduras (UNAH) this could be an effective strategy. This collaboration might expand the EBM frontiers to places that finally have recognized research as an urgent need.